Two King Lears: The meaning potentials of writing and speech for talking books - Lundh, A.H.; Smith, B. (University of Akron, 2015)
The talking book is a type of assistive technology where original print text is audio recorded and marked-up in order to make it accessible for people with print-disabilities, such as visual impairments or dyslexia. In this pilot study, we explore the implications of remediating a written text, the script of Shakespeare’s King Lear, into spoken text. We compare two readings of the play: a talking book version; and a commercial audiobook recording. We examine intonation choices in an excerpt from the play in the two readings. The analysis shows significant variation in choices of intonation, and thus the meanings that are produced in the two versions, resulting in not one but two King Lear plays. One implication of such variation might be that different styles of narration demand different ways of reading. The results point to the need to explore how intonation makes meaning for actual talking book readers in situ, where meaning-potentials are realised through the interaction and encounter between the text, the reader(s), the social settings in which they are reading, and the material properties of talking books.